Immune checkpoints indoleamine 2, 3‐dioxygenase 1 and programmed death‐ligand 1 in oral mucosal dysplasia. (20th June 2018) - Sieviläinen, Meri; Passador‐Santos, Fabricio; Almahmoudi, Rabeia; Christopher, Solomon; Siponen, Maria; Toppila‐Salmi, Sanna; Salo, Tuula; Al‐Samadi, Ahmed
Abstract : Background: Oral mucosal dysplasia is a histologic feature of potentially malignant disorders that is associated with the risk of transformation to carcinoma. Dysplastic cells use many strategies during their transformation to cancer, including escape from the immune mediated destruction. We hypothesized that adaptive immunity is inhibited by activation of distinct immune checkpoint molecules, such as indoleamine 2, 3‐dioxygenase 1 (IDO1) and programmed death‐ligand 1 (PD‐L1). Methods: We collected 63 oral dysplasia samples from 47 patients. Nine biopsies from alveolar mucosa were taken during wisdom teeth extractions were used as healthy controls. Tissue samples were stained and scored for IDO1 and PD‐L1. Additionally, dysplasia grades and inflammatory cell infiltration were evaluated. Eight patients were followed up to 36 months to evaluate dysplasia progression, inflammation, and immune checkpoint molecules expression. Results: Dysplastic epithelium had significantly lower IDO1 expression than that of healthy controls. PD‐L1 positive cells in the lamina propria were mainly in dysplastic samples and seldom in healthy controls. Dysplasia grade was associated negatively with epithelium IDO1 and positively with IDO1 and PD‐L1 expression in the lamina propria. There was a positive association between dysplasia grade and level of inflammatory cell infiltration. During follow‐up, dysplasia grade, inflammatory cell infiltration, and the immune checkpoint expression fluctuated over time. Conclusions: Immune checkpoint molecules IDO1 and PD‐L1 are modulated during oral epithelial dysplastic changes, and their expression is associated with inflammatory cell infiltration in the lamina propria. As immune checkpoint molecules expression fluctuates over time, these molecules are not useful as biomarkers for oral mucosal dysplasia progression.